Mobile Applications: Blend of ICT and Mobile technology for Modern Libraries and services (LIS TODAY, 2021)
This paper covers a brief introduction about mobile technology and its implementation in  libraries. It describes how mobile technology can be used in different areas of library and its services  to provide excellent services to its users. Further the paper describes mobile applications available  for libraries and its users and some national and internationally renowned useful mobile based  library applications, websites for creating mobile applications, mobile applications for users/learners  etc.
Keywords: Mobile Application; Mobile Technology; Mobile Application in Libraries; ICT and Libraries